2019
DOI: 10.3390/electronics8060672
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Low-Level and High-Level Intuitive Features for Melanoma Detection

Abstract: This paper presents an intelligent approach for the detection of Melanoma—a deadly skin cancer. The first step in this direction includes the extraction of the textural features of the skin lesion along with the color features. The extracted features are used to train the Multilayer Feed-Forward Artificial Neural Networks. We evaluate the trained networks for the classification of test samples. This work entails three sets of experiments including 50 % , 70 % and 90 % of the data used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…To completely assess the proposed approach, some reported data on the classification performance previously published on this topic are discussed. Ashfaq et al [ 33 ] associated the ABCD features with GLCM parameters and trained a Multilayer Feedforward Artificial Neural Network. However, in the reported results, there was no noticeable enhancement as compared to using ABCDE features alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To completely assess the proposed approach, some reported data on the classification performance previously published on this topic are discussed. Ashfaq et al [ 33 ] associated the ABCD features with GLCM parameters and trained a Multilayer Feedforward Artificial Neural Network. However, in the reported results, there was no noticeable enhancement as compared to using ABCDE features alone.…”
Section: Resultsmentioning
confidence: 99%
“…They were correlated into two steps: in a first step, segmentation and a coarse classification were performed, and in the next step, a refinement of the coarse classification results was done by distance heat-map computation. In another paper, GLCM and color features of the lesion were combined and further used to train a Multilayer Feedforward Artificial Neural Network [ 33 ] for skin cancer detection. An accuracy of 93.7% for melanoma detection was reported for a total number of 206 images (119 melanoma and 87 non-melanoma type).…”
Section: Related Workmentioning
confidence: 99%
“…For feature extraction, the Lesion Feature Network framework has been used. The authors in [30] connected the information about texture (features extracted from gray level co-occurrence matrix) with the information about shape and color (ABCD rule) at the entrance of an artificial neural network and obtained a detection of melanomas with an accuracy of 93.7%. Just as [18] and [28], we use information about texture, color and shape, but on separate channels.…”
Section: Related Workmentioning
confidence: 99%
“…In total, 15 images were taken for testing, 5 images each for glaucoma, DR and healthy images [19,24]. There have been several studies reported in the literature for classifying retinal images with various preprocessing methods in combination with machine learning techniques; a comprehensive review and details are provided in [25][26][27][28]. As stated in [28], Niemeijer et al used the probability of finding pixels by Gaussian filters.…”
Section: Backend Recognition Using a Neural Classifiermentioning
confidence: 99%